Characterization on the glass forming ability of metallic nano-glasses by the dynamic scaling for mechanical loss in supercooled liquid state. (October 2021) - Li, Tian; Shen, Ying; Zheng, Guangping
Abstract: Metallic nano-glasses (NGs) are promising in solving the issues of metallic glasses (MGs) such as the intrinsic size limitation and low tensile ductility, while the understanding on the forming ability of glassy structures in NGs is still lacking. Herein, an exponent β is proposed to characterize the glass forming ability (GFA) of NGs, as well as MGs, which is determined by dynamic scaling for mechanical losses ( Q   −   1 ) with the frequency ω of external perturbation in their supercooled liquid states as Q   −   1 ~ω −β . The results suggest β is more accurate and sensitive than other commonly used parameters in measuring GFAs, and confirm NGs with a higher volume fraction of glass-glass interfaces (GGIs) have more thermodynamically stable glass phases and enhanced GFAs with higher β values. Our findings provide solid evidence that the introduction of GGIs in NGs could resolve the longstanding issue of size limitation on MGs. Graphical abstract: Image, graphical abstract